Hermeneutic Approach to Quantum Learning - Ehsan Sabaghi Noushabadi; Hassan Rastegarpour; Majid AliAsgari (Journal of Philosophical Investigations, 2021)
This paper aims to discover the key components of quantum theory in learning through hermeneutic research method. Quantum theory is exactly against the theory of simplicity. While the theory of simplicity has been influenced by modernity and the insights from Descartes and Newton who believe that phenomena can be reduced to their simplest form, quantum theory emphasizes holism and holds that all the components of being are dynamic and interconnected. Cartesian reductionism led to the linear causality between phenomena, which believed that phenomena were predictable and controllable, and therefore certain, but the Quantum perspective instead focused on the complexity and entanglement of relationships rather than on linearity and simplicity. Discussions on Quantum learning were started by quantum theory. Emphasizing on holism, entanglement, and the complex interactive relationship between phenomena, they focused on both objective and extrinsic capacities as well as subjective and intrinsic capacities. This perspective of Quantum thinking leads to cooperative learning, dynamic classrooms, learning through conscious and subconscious memory, data processing and conceptualization, input data processing cycles, visual learning, auditory and motor- sensory learning, subjective learning and consideration of learning context, which all consider holism and entanglement in learning.